2016
DOI: 10.1002/elan.201600152
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Biosensor for Naphthalene Acetic Acid in Fruits and Vegetables Based on Lipid Films with Incorporated Auxin‐binding Protein Receptor Using Graphene Electrodes

Abstract: The present work describes a miniaturized potentiometric naphthalene acetic acid (NAA) sensor on graphene nanosheets with incorporated lipid films. Auxin‐binding protein 1 receptor immobilized on the stabilized lipid films provided adequate selectivity for detection over a wide range of hormone concentrations, fast response time of ca. 5 min, and detection limit of 10 nM. The proposed sensor is easy to construct and exhibits good reproducibility, reusability, selectivity, long shelf life and high sensitivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…The supported lipid films were modified by calixarenes and permitted sensitive and rapid determination of insecticides in fruits and vegetables [19]. Other applications in this field include the construction of a disposable chemosensor for the selective fast detection of food hormones (i.e., naphthalene acetic acid) in fruits and vegetables [20] and of zinc in waters [21].…”
Section: Applications Of Lipid Film Based Biosensors In Food Analysismentioning
confidence: 99%
“…The supported lipid films were modified by calixarenes and permitted sensitive and rapid determination of insecticides in fruits and vegetables [19]. Other applications in this field include the construction of a disposable chemosensor for the selective fast detection of food hormones (i.e., naphthalene acetic acid) in fruits and vegetables [20] and of zinc in waters [21].…”
Section: Applications Of Lipid Film Based Biosensors In Food Analysismentioning
confidence: 99%
“…A miniaturized potentiometric naphthalene acetic acid (NAA) sensor on graphene nanosheets with incorporated lipid films was reported recently [33]. Auxin-binding protein 1 receptor immobilized on the stabilized lipid films provided adequate selectivity for detection over a wide range of hormone concentrations, fast response time of ca.…”
Section: Examples Of Biosensors Based On Lipid Modified Graphene Micrmentioning
confidence: 99%
“…The results of Raman and IR showed that the polymerization kinetics ended after four hours. The polymerization mechanism and generation of the signal was further on explored by Raman and IR spectroscopy, micro-Raman spectroscopy, DSC, and SEM experiments [2,3,9,10]. These membranes were stable for storage in air for a period of longer than two months.…”
Section: Polymer Lipid Membranesmentioning
confidence: 99%
“…A naphthalene acetic acid (NAA) potentiometric device, using the described graphene electrode in which the lipid membrane transducer was deposited, has been described in the literature [2]. The receptor (auxin-binding protein 1) was placed in the lipid mixture prior to polymerization.…”
Section: Potentiometric Applications On Biosensors Based On Lipid Memmentioning
confidence: 99%
See 1 more Smart Citation